Upaya Guru Suluk (Akhlak) Dalam Meningkatkan Belajar Siswi Madrasah Tsanawiyah - Yani, Sarifah Novi; Suhartono, Suhartono (An-Nuha, 2026)
This study aims to describe the efforts of a suluk (morals) teacher to improve the learning focus of eighth-grade female students at MTs Pondok Pesantren Al-Furqon Putri Paser. This study used a descriptive qualitative approach using observation, interviews, and documentation techniques. The results indicate that the suluk teacher employed various coaching strategies: fostering etiquette before learning, engaging students with lack of focus, creating a conducive classroom atmosphere, and instilling the value of muraqabah (feeling God's watchful eye). The teacher also integrated moral values such as sincerity, contentment, and asceticism (zuhud) to enable the students to maintain concentration and avoid distraction. The impact of these efforts was seen in increased student participation, discipline, and spiritual awareness in learning. These findings confirm that moral development by the suluk teacher significantly contributes to improving the learning focus of female students in the Islamic boarding school environment.